Analisis Keberhasilan Pengobatan Pasien TB Paru dan TB HIV di Rumah Sakit Penyakit Infeksi Sulianti Saroso - Andayani, Nurita; Maninda, Raise; Marlina, Rosa; Noviantani, Qoina; Qalalwa, Khaled (Faculty of Pharmacy, Universitas Pancasila, 2023)
Mycobacterium tuberculosis causes Tuberculosis (TB), an infectious disease. The study aims to evaluate DOTS therapy's impact on pulmonary TB and TB-HIV patients. This research used a descriptive qualitative study design with a retrospective descriptive research approach using secondary data for the period June 2017 to July 2020. The analysis uses the Miles and Huberman model. A study of 305 people found that 83% of pulmonary TB cases completed treatment within the initial phase, 64% completed the continuation phase. TB-HIV cases 93% completed treatment within the initial phase, 71% the continuation phase. The combination of OAT and ARV doses was successful in reducing initial smear conversion in pulmonary TB cases. The treatment was evaluated as cure in pulmonary TB cases, complete in pulmonary TB-HIV cases, and had no treatment failure status in both groups. Treatment success in pulmonary TB patients was not significantly related (p-value≥5%) with the type of OAT, type of PMO, gender, and age. Whereas in HIV co-infected pulmonary TB patients, treatment success was significantly related (p-value <5%) with the type of PMO, and not related (p-value≥5%) with the type of OAT, gender, and age.